Preparation and Physico-Chemical Characterisation of VPO and V₂O₅/TiO₂ Catalysts - Goh, Chee Keong (2002)
Vanadium-based catalyst plays an important role in petrochemical industry in this study, two types of vanadium-based catalysts were synthesised They are vanadium phosphorus oxide and vanadia-titama catalyst. Vanadium phosphorus oxide catalysts were synthesised via two different precursors.